(untitled) (Моделювання, керування та інформаційні технології, 2019)
This work is devoted to the problems of recognition of discrete objects. It continues a series of articles devoted to the study of recognition systems in the form of logical trees, optimization of synthesized systems of classification of discrete objects, studies of their maximum complexity and the possibility of building effective methods to minimize them. Here the scheme of construction of system of recognition of discrete objects on the basis of a logical tree is step by step considered, and in the center of research there is a graph-circuit model of system of recognition in the form of a logical tree. Note that the results of this robot are relevant for all pattern recognition problems, in which the resulting recognition scheme can be represented as a logical tree.